Lysophosphatidic Acid Pretreatment Attenuates Myocardial Ischemia/Reperfusion Injury in the Immature Hearts of Rats - Chen, Haibo; Liu, Si; Liu, Xuewen; Yang, Jinjing; Wang, Fang; Cong, Xiangfeng; Chen, Xi (Frontiers in Physiology, 2017)
The cardioprotection of the immature heart during cardiac surgery remains controversial due to the differences between the adult heart and the newborn heart. Lysophosphatidic acid (LPA) is a small bioactive molecule with diverse functions including cell proliferation and survival via its receptor: LPA1-LPA6. We previously reported that the expressions of LPA1 and LPA3 in rat hearts were much higher in immature hearts and then declined rapidly with age. In this study, we aimed to investigate whether LPA signaling plays a potential protective role in immature hearts which had experienced ischemia/reperfusion (I/R) injury. The results showed that in Langendorff-perfused immature rat hearts (2 weeks)，compared to I/R group ,LPA pretreatment significantly enhanced the cardiac function, attenuated myocardial infarct size and CK-MB release, decreased myocardial apoptosis and increased the expression of pro-survival signaling molecules. All these effects could be abolished by Ki16425, an antagonist to LPA1 and LPA3. Similarly, LPA pretreatment protected H9C2 from hypoxia-reoxygenation (H/R) induced apoptosis and necrosis in vitro. The mechanisms underlying the anti-apoptosis effects were related to activation of the phosphatidylinositol 3-kinase (PI3K) / protein kinas B (AKT) signaling pathways as well as phosphorylation of the downstream effector of AKT, glycogen synthase kinase 3 beta (GSK3β) ，through LPA1 and/or LPA3. Furthermore, we found that LPA preconditioning increased glucose uptake of H9C2 subjected to H/R by the activation of AMP-Activated Protein Kinase （AMPK）but not the translocation of GLUT4. In conclusion, our study indicates that LPA is a potent survival factor for immature hearts against I/R injuries and has the potential therapeutic function as a cardioplegia additive for infantile cardiac surgery.